Research Priorities for the, Study of Aeolian Activities and Sand Dune Reclamation - Mainguet, Monique (Annals of Arid Zone, 2016)
Rapidly increasing population in the dryland ecosystems and consequent shortages of agricultural land, climate-related threats to food security, especially in Africa, preference given to the strategy for food self-sufficiency and the compulsion of cultivating vulnerable aeolian areas like semi-fixed dunes, sand sheets and loess blankets increase the necessity of research on aeolian activities and sand dune reclamation. The detrimental effects of wind erosion on global environment are not yet well appreciated, because the processes are still not well understood and the initial symptoms are difficult to detect. The human impact on the wind action system is also not fully appreciated. This paper provides a brief history of aeolian research and then identifies the topics which require more studies and verification, like relationship among sand deposits, climate and vegetation cover, development of sand seas in relation to topography, dune orientation, dune building episodes and the concept of sediment balance. Finally, the paper discusses why wind erosion is so difficult to combat, and what knowledge-base is needed for the control measures.